Crime in Italy at the time of the pandemic - Travaini, Guido; Caruso, Palmina; Merzagora, Isabella (Acta Biomedica Atenei Parmensis, 2020)
Background. The beginning of 2020 has been marked by a historic event of worldwide importance: the Coronavirus pandemic. This emergency has resulted in severe global problems affecting areas such as healthcare and the social and economic fields. What about crime? Purpose of the work. The purpose of this work is to reflect about Italy and its crime rate at the time of Coronavirus. Methods. Some crimes will be analysed (the “conventional” ones only, ruling out health-related offences) in the light of data resulting from Ministries and Europol reports, as well as from newspapers and news. Results and conclusions. The outcome will be explained, and some criminological remarks will be added.